Поширення самовідновлювальних деревних інтродуцентів на території дендропарку “Тростянець” - Iljenko, O.O.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of study of features and degree of distribution on territory of dendrology park Trostjanets for self-regenerative arboreal introducents are presented. It is chosen the three category on the degree of distribution. By the most numerous group is the category of not widespread introducents – 70.4 %, the category of middle-spread species is 18.5%, the most widespread – 11.1%. In terms of quantity in all categories the spontaneously widespread species are predominated. Among that most active are Parthenocіssus quіnquefolіa (L.) Planch., Robіnіa pseudoacacіa L., Aesculus hyppocastanum L., Acer pseudoplatanus L. and Thuja occіdentalіs L. Outside of Dendropark Acer negundo L. and Parthenocіssus quіnquefolіa spontaneously are spread.